Multientity Scaling and the Consistency of Country-of-Origin Attitudes - Olsen, Svein Ottar; Olsson, Ulf H. (Journal of International Business Studies, 2002)
This study was particularly designed to respond to Jaffe and Nebenzahl's (1984) suggestion to test whether and how entity-based and attribute-based semantic differential scaling formats could predict purchasing behavior within a country-of-origin setting. The study includes recent research on survey context effects in order to explain and extend our analysis, and uses attitude consistency theory as a conceptual framework. A comparison of the fit statistics between the two scaling formats on each entity (country) indicates that the attribute based format estimates a higher attitude response consistency and predictive validity by giving better predictors of global country image (evaluation) and buying frequency of products from the different countries investigated. This study uses data collected from a probability sample of industrial buyers within the seafood industry.